2019
DOI: 10.3390/ijms20164025
|View full text |Cite
|
Sign up to set email alerts
|

Marine-Derived Omega-3 Polyunsaturated Fatty Acids and Heart Failure: Current Understanding for Basic to Clinical Relevance

Abstract: Heart failure (HF) is a rapidly growing global public health problem. Since HF results in high mortality and re-hospitalization, new effective treatments are desired. Although it remains controversial, omega 3 polyunsaturated fatty acids (n-3 PUFAs), such as the eicosapentaenoic acid and docosahexaenoic acid, have been widely recognized to have benefits for HF. In a large-scale clinical trial regarding secondary prevention of HF by n-3 PUFA (GISSI-HF trial), the supplementation of n-3 PUFA significantly reduce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
52
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(53 citation statements)
references
References 113 publications
(148 reference statements)
0
52
0
1
Order By: Relevance
“…The results of a randomized, double-blind, placebo-controlled study performed on nearly 7000 participants confirmed that supplementation with 1 g of n-3 PUFA daily significantly reduced cardiovascular mortality and admission to hospital for cardiovascular reasons in patients with heart failure [66]. This and other studies have been recently summarized by Sakamoto et al who highlighted some mechanisms of n-3 PUFA protective role in heart failure [67]. They involve direct and indirect actions, such as alterations of metabolic cardiomyocyte conditions or anti-inflammatory properties of PUFA metabolites.…”
Section: Discussionmentioning
confidence: 64%
“…The results of a randomized, double-blind, placebo-controlled study performed on nearly 7000 participants confirmed that supplementation with 1 g of n-3 PUFA daily significantly reduced cardiovascular mortality and admission to hospital for cardiovascular reasons in patients with heart failure [66]. This and other studies have been recently summarized by Sakamoto et al who highlighted some mechanisms of n-3 PUFA protective role in heart failure [67]. They involve direct and indirect actions, such as alterations of metabolic cardiomyocyte conditions or anti-inflammatory properties of PUFA metabolites.…”
Section: Discussionmentioning
confidence: 64%
“…The fatty acid analysis revealed the presence of high levels of n -3 PUFA, namely 22:6 n -3 (DHA, 17.2 ± 2.7%), 18:4 n -3 (SDA, 11.0 ± 0.4%), and 18:5 n -3 (6.6 ± 0.5%), which is in agreement with what has been previously described in literature [ 13 , 56 , 57 , 58 , 59 ]. This profile gives E. huxleyi increased potential as a source of these compounds, which have been described with significant activity in reducing cardiovascular disease, morbidity, and mortality [ 60 , 61 , 62 , 63 , 64 ], as well as visual and neurological development and improvement in inflammatory conditions, such as arthritis and asthma [ 65 , 66 , 67 ].…”
Section: Discussionmentioning
confidence: 99%
“…[ 326 ] with permission from the publisher; B is reproduced from Ref. [ 327 ] with permission from the publisher; C is reproduced from Ref. [ 328 ] with permission from the publisher).…”
Section: Medical Applicationsmentioning
confidence: 99%